UCAPAN LANGSUNG DAN TIDAK LANGSUNG BAHASA INGGRIS DAN BAHASA BUNGKU (SUATU ANALISIS KONTRASTIF) - Karim, Dian Fitriani (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This study is an attempt to identify, analyze, and describe the types of direct and indirect speech in English and Bungku language. In collecting data, the writer describes and identifies the sentences which refers to direct and indirect speech in English and Bungku language. Bungku language are used by the people who lives in Morowali district, especially in Bungku village. The writer also describes the types of direct and indirect in English and Bungku language and find out the similarities and the differences of direct and indirect used the concept of Quirk et al, Marcella Frank and Digby Beaumont descriptively. The result of this investigation shows that not only English has direct and indirect speech but also Bungku language has it. In analyzing the data, the writer uses the theory of Quirk et al (1973), about direct and indirect speech.   ______________________________________________________________________________ Key words:      Direct and Indirect Speech, English and Bungku Language, Contrastive Analysis.